The Influence of the Thyroid Function on the Metabolic Rate of Prothrombin, Factor VII, and Factor X in the Rat - Oosterom, Allan T. van; Mattie, Herman; Hermens, Wim Th; Veltkamp, Jan J. (Thrombosis and Haemostasis, 1976)
The influence of the thyroid function on the metabolic rate of prothrombin, factor VII, and X was studied in the rat. Disappearance rates of the three coagulation factors were measured after synthesis had been blocked with appropriate doses of warfarin, and reappearance rates were assessed upon induction of synthesis by high doses of vitamin K1 injected into rats displaying coumarin induced hypocoagulability.No statistically significant difference in the disappearance and production rates of any of the factors could be found between normal euthyroid rats and thyroxin-treated hypothyroid rats proven to be euthyroid. The differences between the two euthyroid groups and the hypothyroid group were highly significant, however: hypothyroidism results in an approximately 50% decrease of the metabolic rates of the three coagulation factors under study.The reappearance of the three factors, under euthyroid as well as hypothyroid conditions, showed a biphasic pattern: in the first two hours after vitamin K1 administration to warfarin treated rats, a rapid reappearance was observed, to the same extent for all three factors, in hypo- as well as euthyroid rats. This finding suggests that in vitamin K1 deficiency an intracellular accumulation of precursor proteins (PIVKAs) occurs, which after rapid conversion into biologically active coagulation factors by vitamin K1 are shed into circulation.The subsequent phase of reappearance is much slower and reflects the synthesis rate of coagulation enzymes. It is characteristic for each factor and clearly slower in hypothyroid rats than in euthyroid rats. From this an influence of thyroid function on the synthesis rate of the protein moiety of coagulation factors can be inferred.An apparent difference between disappearance and reappearance rate of the coagulation factors in the plasma, particularly pronounced for factors VII and X in euthyroid rats, could theoretically be explained as the consequence of the model used for derivation of these rates.